Exploring the Contribution of B.Ed. (Hons) Programme in Preparing Prospective Educators for their Professional Roles (Journal of Education and Educational Development, 2023)
This research employs an exploratory case study design within the qualitative paradigm of educational research. The study has been conducted in one of the private teacher education institutes in Karachi. On HEC’s notification of phasing out of 1-year B.Ed., the institute offered B.Ed. (Hons) degree programme in affiliation with the Karachi University. The first cohort of B.Ed. (Hons) is working at different educational institutes. This study was carried out to explore the contribution of the B.Ed. (Hons) programme in preparing prospective educators for their professional responsibilities. Employing a qualitative research method allowed the researcher to transmit the ideas, experiences and testimonies of the B.Ed. (Hons) graduates.Reflecting on their experiences, graduates have acknowledged the contribution of different aspects of the programme including learning from the compulsory and enrichment courses, exposure of academic and co-curricular activities, research and field work experiences of teaching etc. creating an impact in their professional lives. The perceived experiences of the participants show that learning from B.Ed. (Hons) has helped them change their perspectives of teaching and learning, provided them with greater opportunities at the workplace and helped them to meet their professional responsibilities and commitments. The study recommends continuation of providing support mechanisms and enrichment courses for the student body.